Space-Time Permutational Scan Statistics untuk Mendeteksi Hotspot Kejadian Gempa Bumi di Sulawesi Tengah - Hasnul Yakin; Muhammad Kasim Aidid; Muhammad Nusrang (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2019)
Abstract. Space-Time permutation scan statistics is a point grouping method based on space and time to identify an event (hotspot) to be spread evenly in every area or have grouping in a certain area and statistically significant. This method is applied for case data only. Hotspot is defined as something unusual, anomalies, case deviations, outbreaks of a disease, a high group or also called a critical area. This research used an earthquake incidence data in Central Sulawesi in 2017-2018. This analysis obtained 3 hotspots but only 2 hotspots were statistically significant with p-value of less than 0.05. The two hotspots are the main hotspots which cover Donggala Regency, Palu City, and Parigi Moutang Regency, while secondary hotspots include Sigi Regency and Poso Regency.